Combined effect of genetic polymorphisms of AURKA and environmental factors on oral cancer development in Taiwan - Chou, Chia-Hsuan; Chou, Ying-Erh; Chuang, Chun-Yi; Yang, Shun-Fa; Lin, Chiao-Wen (PLOS ONE, 2017)
Oral squamous cell carcinoma (OSCC) is the sixth and fourth most common cause of cancer death in men worldwide and in Taiwan, respectively. AURKA, which encodes a centrosome-related serine/threonine kinase, is frequently amplified and overexpressed in many human cancers, particularly advanced OSCC. We conducted a hospital-based case-control study to estimate AURKA single-nucleotide polymorphisms (SNPs) and environmental risk factors to determine OSCC susceptibility and clinicopathological characteristics. We enrolled a total of 876 OSCC patients and 1200 controls. Four SNPs of AURKA, namely rs1047972, rs2273535, rs2064863, and rs6024836, were analyzed using real-time polymerase chain reaction (PCR). Among the 1420 smokers, the AURKA polymorphism carriers with the betel nut chewing habit had a higher risk of oral cancer than AURKA wild-type (WT) carriers without the betel nut chewing habit. Patients with the AURKA rs2064863 gene had a 1.365-fold higher risk of stage III or IV OSCC (95% confidence interval [CI] 1.029-1.811) than those with the rs2064863 WT gene. Furthermore, carriers of the AURKA rs1047972/rs2273535/rs2064863 C-A-T haplotype had a 1.736-fold (95% CI 1.110-2.715) higher risk of OSCC than controls (C-T-T, the most common haplotype). Among patients with the betel quid chewing habit, carriers of other haplotypes (C-T-T, C-A-G, T-A-T, T-A-G, T-T-T, and C-T-G) had a 12.857-fold (95% CI 10.731-15.404) increased risk, and carriers of the C-A-T haplotype had the highest risk (AOR: 31.120; 95% CI 13.864-69.850) of OSCC, compared with those without the betel quid chewing who harbored other haplotypes. In conclusion, betel nut chewing combined with the AURKA C-A-T haplotypes lead to a high risk of OSCC. These findings reveal a novel genetic-environmental predisposition for oral tumorigenesis.